Multilateral Productivity Comparisons When Some Outputs are Undesirable: A Nonparametric Approach - Faere, Rolf; Grosskopf, Shawna; Lovell, C. A. K.; Pasurka, Carl (The Review of Economics and Statistics, 1989)
Rolf Faere, Shawna Grosskopf, C. A. K. Lovell, Carl Pasurka, Multilateral Productivity Comparisons When Some Outputs are Undesirable: A Nonparametric Approach, The Review of Economics and Statistics, Vol. 71, No. 1 (Feb., 1989), pp. 90-98